2016
DOI: 10.3389/fncel.2016.00233
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Conductances during Interictal Discharges in Pyramidal Neurons of Rat Entorhinal Cortex

Abstract: In epilepsy, the balance of excitation and inhibition underlying the basis of neural network activity shifts, resulting in neuronal network hyperexcitability and recurrent seizure-associated discharges. Mechanisms involved in ictal and interictal events are not fully understood, in particular, because of controversial data regarding the dynamics of excitatory and inhibitory synaptic conductances. In the present study, we estimated AMPAR-, NMDAR-, and GABAA R-mediated conductances during two distinct types of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 66 publications
11
50
0
Order By: Relevance
“…We used a linear function for AMPAR-mediated current and the Boltzmann function (Jahr and Stevens, 1990 ; Harnett et al, 2015 ) for NMDAR-mediated current. The main difference of this approach from the one utilized in our previous study (Amakhin et al, 2016 ) is that reference I-V relationship for NMDAR-mediated current ( f NMDA ( U ) in Equations (1) and (2) was not pre-recorded in a separate set of experiments but was obtained for every recorded cell individually, thus allowing us to account for slight variations of individual shape of I-V relationships in order to perform a more accurate estimation of synaptic conductances. I-V curves for isolated NMDAR-mediated currents were obtained in presence of inhibitors of GABAA (bicuculline) and AMPA (DNQX) receptors.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We used a linear function for AMPAR-mediated current and the Boltzmann function (Jahr and Stevens, 1990 ; Harnett et al, 2015 ) for NMDAR-mediated current. The main difference of this approach from the one utilized in our previous study (Amakhin et al, 2016 ) is that reference I-V relationship for NMDAR-mediated current ( f NMDA ( U ) in Equations (1) and (2) was not pre-recorded in a separate set of experiments but was obtained for every recorded cell individually, thus allowing us to account for slight variations of individual shape of I-V relationships in order to perform a more accurate estimation of synaptic conductances. I-V curves for isolated NMDAR-mediated currents were obtained in presence of inhibitors of GABAA (bicuculline) and AMPA (DNQX) receptors.…”
Section: Discussionmentioning
confidence: 89%
“…To assess the relative impacts of AMPA and NMDA receptors during evoked response in each neuron, we implemented the mathematical approach described in our previous study (Amakhin et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Certain kind of interictal and preictal discharges are based on the recurrent interactions of only excitatory neurons [ 2 ], [ 10 ] whereas the mechanisms of other discharges have suggested that interneurons are strongly involved [ 11 ], [ 10 ], [ 4 ], [ 12 ], [ 13 ]. Using 4-aminopyridine (4-AP) in vitro epilepsy model [ 14 ], we distinguished two basic types of IIDs: IID1s, which are mediated by GABA, and IID2s, which are mediated by both GABA and glutamate. The depolarizing effect of GABA may cause the generation of epileptiform events.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that some convulsants trigger an intense firing of interneurons, which enhances GABA release [ 15 ] increases intracellular chloride concentration and may switch GABA responses to depolarization [ 16 ], [ 17 ], [ 18 ], [ 13 ]. In our previous work, a synchronous interneuronal activity with IIDs has been described, that evoked by using 4-AP, high potassium in vitro model [ 14 ]. Similar events were referred to as GABA-mediated, slow interictal potentials by [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation